Interpersonal Ethical Principles in the Qur'an: A Contextual Analysis of Social Moral Values in Islamic Scripture - Muhammad Nur Wahid; Ahmad Nurrohim; Hamzah Al-Haqqoni (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: Identify and interpret the ethical values contained in Surah Al-Hujurat verses 6–12 and analyze their application in daily life and broader social structures. Theoretical framework: A theoretical framework based on Islamic social ethics sourced from the Qur'an, especially the values of information verification (tabayyun), justice in conflict resolution, brotherhood, and prohibition of ridicule, prejudice, and ghibah. Literature review: A literature study that includes the Qur'an, classical and contemporary commentaries, and modern social science literature that addresses ethical and communication challenges in today's Muslim society. Methods: Qualitative research with a thematic interpretation approach (tafsīr maudhū'ī) combined with contextual-sociological analysis, with data collected through literature studies. Results: It was found that the ethical values in Surah Al-Hujurat are not only normative but also highly relevant and applicable in the context of today's digital and multicultural society. The five main values identified are: information verification, conflict resolution, social solidarity, respect for human dignity, and prejudice control. Implication: This study recommends the integration of these Qur'anic ethical values into character education, social policy, and ethical communication practices in society. Novelty: The novelty of this study lies in the contextual analysis of the application of social ethical values in Surah Al-Hujurat in contemporary digital and multicultural societies, an approach that is rarely discussed in the study of social interpretation in depth.